Plant communities supported by the geological setting: the case history of the Isole dei Ciclopi (east Sicily) - Sciandrello, Saverio; Minissale, Pietro; Sturiale, Giovanni (Lazaroa, 2017)
This paper provides an update inventory of the vascular flora and a framework of the plant communities of the Isole dei Ciclopi (Acicastello, Catania) taking into account their geological setting. A total of 111 phytosociological relevés were performed in the period 2015-2016. The plant communities has been analyzed using WPGMA and Euclidean distance classification. The study area preserves interesting plant-communities, mainly represented by shrubs vegetation (Oleo-Ceratonion siliquae and Pruno-Rubion ulmifolii), rocky coast communities (Crithmo-Staticion), cliff vegetation (Anthyllidion barbae-jovis), halo-nitrophilous vegetation (Pegano-Salsoletea), spring-flowering meadows (Frankenion pulverulentae) and nitrophilous communities (Allion triquetri and Echio-Galactition tomentosae). The vegetation analysis allow the identification of twelve vegetation types and also the reconstruction of three vegetation series. The collected data have been organized in a GIS and the following thematic maps have been produced: vegetation map, habitats map (according to the 92/43/EEC Directive). According to directive 92/43/EU, only three habitat types were delimited through the phytosociological assessment of the plant communities. The flora of the investigated area consists of 102 taxa. The majority of the taxa represented in the life form spectrum are therophytes and hemicryptophytes. From a chorological point of view, the Mediterranean element outweighs the rest, followed by the most diverse group of widespread taxa. Furthermore a detailed geological investigation was carried out and a geological sketch map was performed. The comparison between the vegetation and geological maps shows a good correlation, mostly regarding the distribution of the plant communities onto the different types of substrata.